2010
DOI: 10.1097/fjc.0b013e3181d3da01
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Protects Rat Myocardium Against Isoproterenol-Induced Ischemic Injury: Attenuation of Ventricular Dysfunction Through Increased Expression of Hsp27 Alongwith Strengthening Antioxidant Defense System

Abstract: This investigation examines the role of heat shock protein (Hsp) 27 and its modulation by curcumin in isoproterenol-induced myocardial ischemic injury in rats. Evidence from hemodynamic functions and oxidative stress parameters were also included in the study. The animals were divided into control, isoproterenol, and curcumin 100, 200, and 400 mg/kg treatment groups. Curcumin was administered orally for 15 days to all the treated groups. On 13th and 14th day, isoproterenol (85 mg/kg, s.c.) was injected to curc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 60 publications
2
27
0
1
Order By: Relevance
“…Tanwar et al (2010) demonstrated that CUR protected the heart from ischemic damage and restored cardiac functions by strengthening of the antioxidant defense system (Tanwar et al 2010). In our study, we found that the abilities of CUR or THU to improve hemodynamic status and restore vascular responsiveness are concomitant with the recoveries of eNOS protein expression in aortic tissue and plasma nitrate/nitrite level.…”
Section: Discussionmentioning
confidence: 75%
“…Tanwar et al (2010) demonstrated that CUR protected the heart from ischemic damage and restored cardiac functions by strengthening of the antioxidant defense system (Tanwar et al 2010). In our study, we found that the abilities of CUR or THU to improve hemodynamic status and restore vascular responsiveness are concomitant with the recoveries of eNOS protein expression in aortic tissue and plasma nitrate/nitrite level.…”
Section: Discussionmentioning
confidence: 75%
“…Curcumin has been reported to attenuate liver injury induced by diverse hepatotoxicants [39,40,41] via multiple mechanisms. The two doses of curcumin selected in this study were based on previous studies in which curcumin showed protective effect against oxidant damage in the heart [42], liver [43], and kidney [44]. Its efficacy in protecting against liver injury has been established by its antioxidant or free radical-scavenger action.…”
Section: Discussionmentioning
confidence: 99%
“…12 For instance, curcumin not only inhibits cyclooxygenase-2, lipoxygenase and inducible nitric oxide synthase but also induces heat shock proteins that confer cytoprotection against different stimuli. 35,36 In addition, curcumin possesses well-established antioxidant and free radical scavenging activity which enables it for effective prevention of membrane lipid peroxidation as well as oxidative DNA damage and resulting genotoxicity. 37 We have previously shown in the same patients that curcumin supplementation efficiently enhances serum levels of three important enzymatic antioxidants, namely superoxide dismutase, glutathione peroxidase and catalase.…”
Section: Discussionmentioning
confidence: 99%